2018
DOI: 10.1016/j.biopsych.2017.08.022
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Brain Glycine and Glutamate Concentrations in Patients With First-Episode Psychosis Measured by Echo Time–Averaged Proton Magnetic Resonance Spectroscopy at 4T

Abstract: Our findings demonstrate abnormally elevated brain Glu and Gly levels in patients with first-episode psychosis by means of echo time-averaged proton MRS at 4T. The findings implicate dysfunction of N-methyl-D-aspartate receptor and glutamatergic neurotransmission in the pathophysiology of the acute early phase of psychotic illnesses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 47 publications
1
20
0
2
Order By: Relevance
“…Regarding inhibitory neurotransmission, a recent meta-analysis of 1 H-MRS studies investigating GABA levels across psychiatric conditions (Schur, et al 2016) report reduced GABA levels in symptomatic depressed patients and in patients with schizophrenia relative to healthy controls. These findings provide further support for E/I neurotransmitter imbalance in MDD and schizophrenia, supported by more recent studies which all report aberrant metabolite levels in schizophrenia and psychosis (Dwyer, et al 2018;Jelen, et al 2018;Psomiades, et al 2018;Reid, et al 2019;Kim, et al 2018;Singh, et al 2018). However, currently there is no evidence for differences in GABA levels between healthy controls and patients with bipolar or anxiety disorders (Schur, et al 2016 concentrations have also been shown to predict local activation during a word memory task, an association that appears to be absent in a CHR cohort ).…”
Section: Network Interactions and Excitatory/inhibitory Neurotransmitsupporting
confidence: 73%
“…Regarding inhibitory neurotransmission, a recent meta-analysis of 1 H-MRS studies investigating GABA levels across psychiatric conditions (Schur, et al 2016) report reduced GABA levels in symptomatic depressed patients and in patients with schizophrenia relative to healthy controls. These findings provide further support for E/I neurotransmitter imbalance in MDD and schizophrenia, supported by more recent studies which all report aberrant metabolite levels in schizophrenia and psychosis (Dwyer, et al 2018;Jelen, et al 2018;Psomiades, et al 2018;Reid, et al 2019;Kim, et al 2018;Singh, et al 2018). However, currently there is no evidence for differences in GABA levels between healthy controls and patients with bipolar or anxiety disorders (Schur, et al 2016 concentrations have also been shown to predict local activation during a word memory task, an association that appears to be absent in a CHR cohort ).…”
Section: Network Interactions and Excitatory/inhibitory Neurotransmitsupporting
confidence: 73%
“…This is consistent with the majority of findings from previous 1 H-MRS studies in minimally-medicated or antipsychoticnaïve first episode patients 14,18,[56][57][58][59][60] and a recent meta-analysis 61 although one study has reported greater ACC glutamate in patients than controls. 62 Glutamine and the glutamine/glutamate ratio may be elevated in first episode psychosis, 18,57,58 To our knowledge, this is the first published multi-centre 1 H-MRS study in schizophrenia.…”
Section: Discussionmentioning
confidence: 97%
“…Thus, some patients may be genetically biased much more towards glutamatergic dysfunction than others. Second, sub‐grouping to enrich for patients with likely glutamatergic pathology could be accomplished through genotyping (polygenic scores) and assessment of other informative biomarkers, such as cortical glutamate measured by magnetic resonance . Third, additional strategies to reduce variance would be to: focus on clinics that have ‘real’ patients and not volunteers recruited by advertisements, reduce the number of sites with larger numbers of patients, and focus on the early stages of schizophrenia as chronic patients likely have a different pathology …”
Section: Treatment Based On Glutamate Hypothesismentioning
confidence: 99%